MOBILE DEVOPS PLAYBOOK a practical guide for delivering high-quality mobile applications like a pro - Nabil, Moataz (Packt Publishing Ltd., 2023)
Learn to use mobile DevOps for faster, more efficient mobile development by uncovering the secrets of mobile application development lifecycle Key Features Discover best practices and mobile DevOps tools for test automation, app releases, performance optimization, security, error tracking, and more Enhance efficiency, speed, and quality of your development process with mobile DevOps Explore mobile DevOps components like continuous integration, testing, deployment, and monitoring Purchase of the print or Kindle book includes a free PDF eBook Book Description To build mobile apps, you need to understand mobile-first features, tools, and processes that help you build, test, and release robust apps faster and more efficiently. The multitude of challenges stemming from mobile development's inherent complexities, including native iOS and Android app creation, cross-platform frameworks, and the implementation of scalable architectures within extensive teams, collectively contribute to a substantial number of obstacles that can significantly prolong the release process. This book will help you understand and implement the best practices of mobile DevOps for continuous integration, testing, delivery, deployment, and monitoring. You'll explore different challenges faced by developers due to varied OSs, the unforgiving nature of mobile applications, and continuous updates to mobile phones and learn how to maneuver through these challenges. You'll also get to grips with the latest trends while discovering the potential future of mobile DevOps, with valuable insights and guidance about integrating mobile development teams into your organization. By the end of this book, you'll be well-equipped to successfully implement mobile DevOps and build fast, qualitative, and efficient mobile apps for your team or organization. What you will learn Discover the principles, components, and concepts of mobile DevOps Develop a successful mobile CI/CD strategy in your organization Identify the tools and processes for mobile app release and distribution Develop and release mobile applications efficiently and reliably Implement continuous testing with mobile DevOps Leverage Mobile DevSecOps to improve security, efficiency of your Mobile app development process Understand how Platform Engineering and IDP Teams can improve Developer Productivity in Mobile DevOps Identify and fix problems with mobile application performance and data usage Who this book is for This book is for DevOps engineers looking to learn more about mobile DevOps to build effective processes for releasing mobile apps quickly and frequently. It's also an excellent resource for mobile developers, mobile release managers, mobile architects, mobile platform engineers, and QA engineers, involved in mobile app development. Familiarity with DevOps and mobile app challenges related to testing, releasing, and monitoring especially at scale is a prerequisite.